Detection of expression of IL-18 and its binding protein in Egyptian pediatric immune thrombocytopenic purpura. (May 2014) - Shaheen, Iman A.; Botros, Shahira K. A.; Morgan, Dalia S.
Abstract Immune thrombocytopenic purpura (ITP) is an autoimmune disorder, characterized by dysfunctional cellular immunity including the presence of activated platelet specific autoreactive T cells that recognize and respond to autologous platelet antigens. Autoreactive T cells drive the generation of platelet reactive autoantibodies by B cells as well as T-cytotoxic cell-mediated lysis of platelets. Interleukin-18 (IL-18) is a mediator of T helper type 1 cell responses synergistically with IL-12 that initiate and promote host defense and inflammation. IL-18 has a specific binding protein (IL-18BP) which belongs to the immunoglobulin superfamily. In the present study, serum level and messenger RNA( mRNA) expression of IL-18 as well as IL-18BP mRNA expression were measured in peripheral blood mononuclear cells (PBMNCs) of 100 Egyptian pediatric patients with ITP (70 acute and 30 chronic). In addition to this, we recruited 80 healthy volunteers in order to investigate the possible association between the imbalance of IL-18 and IL-18 BP expressions and the pathogenesis of ITP. IL-18 serum level and mRNA expression were not elevated in cases more than in the control group, but IL-18 mRNA was higher in chronic cases when compared to the acute ones (p = 0.031) and there was a good negative correlation between the platelet count and serum IL-18. IL-18 BP m-RNA was slightly elevated in cases more than in the control group (95% Confidence interval = 1.15–2.01). Our results were not supportive for previous findings of elevated IL18/BP mRNA ratio in ITP patients. This could be referred to the fact that autoimmune diseases are complex genetic disorders, therefore further studies on polymorphisms affecting IL-18 gene expression as well as kinetics of IL-18 expression are required to evaluate the role of interleukin 18 and its binding protein in the pathogenesis of ITP.